Peripheral Ulcerative Keratitis Associated with HCV-Related Cryoglobulinemia - Pedro Coelho; Carlos Menezes; Rita Gonçalves; Pedro Rodrigues; Elena Seara (Case Reports in Ophthalmological Medicine)
Purpose. To describe a case of peripheral ulcerative keratitis associated with type II cryoglobulinemia in the context of Hepatitis C infection. Methods. Case report and literature review. Results. A 36-year-old male patient presented to our emergency department with unilateral moderate pain in his right eye, associated with redness and photophobia. Medical background elicited a history of Hepatitis C and IV illicit drug abuse. Ocular examination revealed a BCVA of 20/30 of the affected eye and slight discomfort with eye movement. Biomicroscopy revealed a ring shaped peripheral corneal ulcer, with a dense white stromal infiltrate sparing the limbus, plus an adjacent area of mild anterior diffuse nonnecrotizing scleritis. No intraocular inflammation was present. Posterior segment was normal. The patient was placed under oral prednisolone (1 mg/Kg/day) with gradual tapering. A dramatic clinical response occurred, with complete resolution of the clinical condition. Systemic analytic workup aiming at autoimmune and infectious diseases was negative, except for high HCV-viral load and the presence of type 2 cryoglobulins. Conclusion. Albeit rare, cryoglobulinemia, even in the absence of systemic vasculitis, should be considered in the differential diagnosis of PUK, when systemic workout for autoimmune diseases is negative.